HYPOGLYCEMIA AWARENESS AND MANAGEMENT STUDY (HAMS) – A RETROSPECTIVE REVIEW OF HYPOGLYCEMIA KNOWLEDGE AMONG HEALTH CARE PROVIDERS IN A SINGLE CENTER - Koh, LP; Tong, CV; Ooi, XY; Maria, AB Dorothy (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Knowledge on management of hypoglycemia is essential for all healthcare providers (HCP). Poor management of hypoglycemia will lead to catastrophic consequences. The objective of this study is to evaluate the level of knowledge on hypoglycemia among HCP in Hospital Melaka. METHODOLOGY This was a retrospective review on level of hypoglycemia knowledge among HCP from various departments. All HCP who attended a Hypoglycemia Roadshow in Hospital Melaka in November 2019 were given an assessment which consisted of 10 questions to evaluate their knowledge on diagnosis, complications and management of hypoglycemia. RESULTS There were 422 participants consisting of 308 doctors and 114 non-doctors. The level of knowledge was divided into low (0-3 points), moderate (4-6) and high (7-10). High scores were seen in 56.16% (n= 237); the rest achieved moderate (35.31%, n=149) and low (8.53%, n=36) scores. We compared the level of knowledge between doctors and non-doctors: 41.94% of doctors achieved high scores as compared to 14.22% of non-doctors. However, this was not statistically significant (p=0.115). HCP from the medical department performed better with 28.67% achieving high scores compared to 27.49% in those from non-medical departments (p=0.00) Numerically, junior HCP (<5 years working experience) performed better with 40.76% obtaining high scores compared to their senior counterparts (≥5 years), with only 15.4% obtaining high scores. (p=0.331) CONCLUSION More than half of the participants had good knowledge on hypoglycemia. Continuing refresher education is important for HCP from all departments regardless of seniority.